La educación en valores, para mejorar la convivencia escolar de los estudiantes del cuarto grado de educación general básica de la escuela “Dra. Matilde Hidalgo de Procel Nro. 2”, sección vespertina, ubicada en el barrio San Pedro, parroquia Sucre, cantón y provincia de Loja, periodo académico 2014-2015 - Granda Apolo, Ximena Anabel (2016)
This research topic called TEACH VALUES TO IMPROVE SCHOOL COEXISTENCE OF FOURTH GRADE STUDENTS OF GENERAL BASIC EDUCATION SCHOOL "DRA Matilde Hidalgo NRO. 2 ", SECTION EVENING, located in Barrio San Pedro, Sucre Parish, Canton and province of Loja, academic period 2014-2015 overall objective was to apply the values in education as a means to improve school life in the Fourth Degree Basic Education parallel "A" School Basic Education "Dra. Matilde Hidalgo No. 2 "2014-2015.; afternoon section located in the Sucre parish, the city of Loja; research was pre-experimental, transversal, descriptive and field for that scientific methods used, analytical, synthetic, deductive, inductive techniques such as direct observation and surveys were applied to 17 students and a teacher type, the which enabled them to obtain accurate and objective information. In this sense, it was shown that students do not promote proper development in the practice of the values inside and outside the classroom, and for them the alternative solutions proposed, the same that helped educate students in values, since this and improving school life, are mutually complementary, are educated in values for peaceful coexistence and values are learned if you have the experience of living in a chord environment with them